Biochemical determinants of nitric oxide synthesis in severe malaria - Alkaitis, M (2014)
Inhibition of nitric oxide (NO) signalling may contribute to the pathogenesis of severe malaria. This thesis examines the impact of Plasmodium infection on three key determinants of nitric oxide synthase (NOS) biochemistry: substrate availability, substrate/inhibitor homeostasis and cofactor availability. Arginine, the NOS substrate, is depleted in human patients with severe Plasmodium falciparum malaria and mice infected with P. berghei ANKA. Using heavy isotope tracer infusions to quantify arginine metabolism in infected mice, we found no evidence of increased catabolism by the enzyme arginase, widely assumed to be responsible for arginine depletion. Genetic knock-out of parasite arginase had no effect on arginine depletion in mice. Instead, our findings link arginine depletion to decreased rates of arginine and citrulline appearance in the plasma of infected mice. Asymmetric dimethylarginine (ADMA) competes with arginine for binding to the NOS catalytic site. We observed elevation of the ADMA/arginine ratio in Gambian children with severe malaria, favouring NOS inhibition. In mice infected with P. berghei ANKA, we found evidence of degradation of dimethylarginine dimethylaminohydrolase 1 (DDAH1), the enzyme primarily responsible for ADMA metabolism. We also observed reduced DDAH activity and accumulation of intracellular ADMA in hepatic tissue of infected mice, suggesting that DDAH dysfunction could contribute to disruption of ADMA/arginine homeostasis. Tetrahydrobiopterin (BH4) is an essential NOS cofactor. In P. berghei ANKA-infected mice, BH4 concentrations were decreased in plasma, erythrocytes and brain tissue, which could inhibit NO synthesis and promote NOS-dependent superoxide production. To reverse deficiencies of NOS substrate and cofactor availability, we infused P. berghei ANKA-infected mice with citrulline, an arginine precursor, and sepiapterin, a BH4 precursor. Restoration of systemic arginine and BH4 availability in infected mice improved whole blood nitrite concentrations, a biomarker of NO synthesis, but did not prevent onset of disease symptoms. These studies have identified biochemical disturbances that may contribute to severe malaria pathogenesis by inhibiting NO synthesis.